Laser-triggered polymeric lipoproteins for precision tumor penetrating theranostics. (November 2019) - Wang, Ruoning; Zhang, Chenshuang; Li, Junsong; Huang, Jinyu; Opoku-Damoah, Yaw; Sun, Bo; Zhou, Jianping; Di, Liuqing; Ding, Yang
Abstract: Natural particles ranging from various cell membranes to nascent proteins are highly optimized for their specific functions in vivo and possess features that are desired in drug delivery carriers. However, the current endeavor in research on bioparticles is still seeking the appropriate strategy to shield multiple agents and circumvent biological hurdles. These issues have propelled the advancement of lipid-polymer hybrid nanocarriers, which could be employed as drug reservoirs and strive to meet these expectations. We thereby proposed functionalized biopeptide-lipid hybrid particles, which were applied to encapsulating a PLGA polymeric core together with indocyanine green (ICG) and packaged by a lipoprotein-inspired structural shell. To initiate precision tumor-penetrating performance, tLyP-1-fused apolipoprotein A-I-mimicking peptides (D4F) were exploited to impart tumor-homing and tumor-penetrating biological functions. The sub-100 nm drug vehicle possessed a long circulation time with uniform mono-dispersity but was stable enough to navigate freely, penetrate deeply into tumors and deliver its cargoes to the targeted sites. Moreover, ICG-encapsulated penetrable polymeric lipoprotein particles (PPL/ICG) could realize real-time fluorescence/photoacoustic imaging for monitoring in vivo dynamic distribution. Upon near-infrared (NIR) laser irradiation, PPL/ICG demonstrated a highly efficient phototherapeutic effect to eradicate orthotopic xenografted tumors, resulting in an 88.77% decrease from the initial tumor volume and inhibited tumor metastasis with good biosafety. Therefore, the described bio-strategy opens new avenues for creating polymeric lipoproteins with varied hybrid functionalities, which may be applied to provide a basis and inspiration for improved nanoparticle-based precision theranostic nanoplatforms. Graphical abstract: Illustration of penetrating polymeric lipoproteins for deep tumor penetration with targeting recognition of cancer cell via dual-modal imaging and effective phototherapy.Image 1